Resource allocation pattern to green technology innovation efficiency: Synergy between environmental resource orchestration and firms' digital capabilities - Rui Zhao; Jing Xu; Yanling Zhao; Yingbin Feng (Journal of Innovation & Knowledge, 2025)
As environmental concerns receive increasing attention, investments in environmental resources have grown, leading to numerous green technology innovations (GTI). Yet, amid limited resources, exploring green technology innovation efficiency (GTIE) becomes a more meaningful topic. Efficient allocation of environmental resources is beneficial for enhancing GTIE. However, in the digital era, the process of digital capabilities in empowering environmental resource orchestration to enhance GTIE remains unclear. Therefore, based on institutional theory and resource orchestration theory (ROT), this study aims to scientifically assess firms’ GTIE and explore the synergy between environmental resource orchestration and firms’ digital capabilities. Malmquist index combined data envelopment analysis (Malmquist-DEA) was used to evaluate the GTIE of firms from a dynamic perspective. Fuzzy-set qualitative comparative analysis (FsQCA) method was utilized to investigate synergy effects. The results reveal that: (1) The constructed input-output indicators provide a comprehensive measure of GTIE, and the listed firms’ GTIE shows an upward trend along time; (2) The synergy between environmental resource orchestration and digital capabilities fosters GTIE through mutual enhancement or compensation of competitive advantages. Specifically, digital capabilities enable the efficient acquisition and deployment of environmental resources, while environmental resource orchestration drives greater demand for digital infrastructure. (3) Their synergy further developed four resource allocation patterns, including Pressure Response Model (PRM) and Active Competitive Model (ACM) associated with High-GTIE, as well as Stereotyped Development Model (SDM) and Blind Development Model (BDM) associated with Nonhigh-GTIE. This research provides beneficial insights and guidelines for governments and corporates to implement GTI practices.